Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Alright, let's find the quadratic function \( f(x) \) given its roots and a point that lies on it.
### Step-by-Step Solution
1. Identify the form of the quadratic function:
Since the function has given roots \( -4 \) and \( 2 \), we can express it in the form:
[tex]\[ f(x) = a(x + 4)(x - 2) \][/tex]
where \( a \) is a constant multiplier that we need to determine.
2. Substitute the given point \( (1, -5) \) into the equation:
This point means that when \( x = 1 \), \( f(x) = -5 \).
So, substitute \( x = 1 \) and \( f(x) = -5 \) into the quadratic equation:
[tex]\[ -5 = a(1 + 4)(1 - 2) \][/tex]
3. Simplify the equation to solve for \( a \):
[tex]\[ -5 = a(5)(-1) \][/tex]
[tex]\[ -5 = -5a \][/tex]
Now, divide both sides by \(-5\) to isolate \( a \):
[tex]\[ a = 1 \][/tex]
4. Substitute \( a \) back into the quadratic equation:
Now that we've determined \( a \) is 1, we can substitute it back into the equation:
[tex]\[ f(x) = 1(x + 4)(x - 2) \][/tex]
Which simplifies to:
[tex]\[ f(x) = (x + 4)(x - 2) \][/tex]
5. Check the options provided:
Given the question's options, the correct one that matches our derived equation is:
[tex]\[ f(x) = (x - 2)(x + 4) \][/tex]
Therefore, the equation of the quadratic function is:
[tex]\[ f(x) = (x - 2)(x + 4) \][/tex]
### Step-by-Step Solution
1. Identify the form of the quadratic function:
Since the function has given roots \( -4 \) and \( 2 \), we can express it in the form:
[tex]\[ f(x) = a(x + 4)(x - 2) \][/tex]
where \( a \) is a constant multiplier that we need to determine.
2. Substitute the given point \( (1, -5) \) into the equation:
This point means that when \( x = 1 \), \( f(x) = -5 \).
So, substitute \( x = 1 \) and \( f(x) = -5 \) into the quadratic equation:
[tex]\[ -5 = a(1 + 4)(1 - 2) \][/tex]
3. Simplify the equation to solve for \( a \):
[tex]\[ -5 = a(5)(-1) \][/tex]
[tex]\[ -5 = -5a \][/tex]
Now, divide both sides by \(-5\) to isolate \( a \):
[tex]\[ a = 1 \][/tex]
4. Substitute \( a \) back into the quadratic equation:
Now that we've determined \( a \) is 1, we can substitute it back into the equation:
[tex]\[ f(x) = 1(x + 4)(x - 2) \][/tex]
Which simplifies to:
[tex]\[ f(x) = (x + 4)(x - 2) \][/tex]
5. Check the options provided:
Given the question's options, the correct one that matches our derived equation is:
[tex]\[ f(x) = (x - 2)(x + 4) \][/tex]
Therefore, the equation of the quadratic function is:
[tex]\[ f(x) = (x - 2)(x + 4) \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.